BIM Application on Sustainable Design (The International Journal of Engineering & Information Technology (IJEIT), 2024)
Sustainable design is a must in today construction industry. However, it needs effective tools to facilitate design decisions from the beginning to the end to save time and avoid any mistakes that might be fatal to green strategies. Building Information Modelling (BIM) is a digital representation of physical and functional characteristics of a facility. As such it serves as a shared knowledge resource for information about a facility forming a reliable basis for decisions during its lifecycle from inception onward. BIM not only brings technical benefits to the development process, but delivers an innovative and integrated working platform to improve productivity and sustainability throughout the project life cycle [Elmualim et al. 2014]. This paper investigates the potentials and possibilities that BIM can add to the sustainable design process through all phases from schematic phase to construction and management phases. The objective of the study is to demonstrate examples and how BIM can make green design decisions easier. The paper also investigates in the integrated process of BIM and its benefits to sustainable design. Finally, it detects the future of the construction industry needs in terms of BIM and what is expected.